2015
DOI: 10.1002/ange.201411858
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of closo‐Borates via Iodonium Zwitterions

Abstract: Asimple method for the functionalization of closoborates [closo-B 10 H 10 ] 2À (1), [closo-1-CB 9 H 10 ] À (2), [closo-B 12 H 12 ] 2À (3), [closo-1-CB 11 H 12 ] À (4), and [3,3'-Co(1,2-C 2 B 9 H 11 ) 2 ] À (5)i sd escribed. Treatment of the anions and their derivatives with ArI(OAc) 2 gave aryliodonium zwitterions,w hichw ere sufficiently stable for chromatographic purification. The reactions of these zwitterions with nucleophiles provided facile access to pyridinium, sulfonium, thiol, carbonitrile,a cetoxy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Recently, we described a simple and efficient pathway to zwitterionic aryliodonium closo-borates, including anions 1a and 2a, and demonstrated their facile transformation to a range of derivatives through a nucleophilic displacement of the iodoarene (Figure 3). 30 We also found that ArI(OAc) 2 exhibits the highest regioselectivity in electrophilic substitution of the anions and, in reactions with anion 2a, gives rise to an ∼1:2 ratio of the 10-vs 6-substituted products, [closo-1-CB 9 H 9 -10-IPh] (5 [10]a) vs [closo-1-CB 9 H 9 -6-IPh] (5 [6]a). This suggested an opportunity to access a broad range of 10substituted derivatives through a direct electrophilic substitution of the cluster, followed by reactions with nucleophiles.…”
Section: ■ Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Recently, we described a simple and efficient pathway to zwitterionic aryliodonium closo-borates, including anions 1a and 2a, and demonstrated their facile transformation to a range of derivatives through a nucleophilic displacement of the iodoarene (Figure 3). 30 We also found that ArI(OAc) 2 exhibits the highest regioselectivity in electrophilic substitution of the anions and, in reactions with anion 2a, gives rise to an ∼1:2 ratio of the 10-vs 6-substituted products, [closo-1-CB 9 H 9 -10-IPh] (5 [10]a) vs [closo-1-CB 9 H 9 -6-IPh] (5 [6]a). This suggested an opportunity to access a broad range of 10substituted derivatives through a direct electrophilic substitution of the cluster, followed by reactions with nucleophiles.…”
Section: ■ Introductionmentioning
confidence: 58%
“…During the reaction, the 5 [6]b isomer was converted to the 6-acetonitrilium zwitterion [closo-1-CB 9 H 8 -1-COOH-6-NCMe] (7 [6]b), which, upon acidic hydrolysis, gave amino acid [closo-1-CB 9 H 8 -1-COOH-6-NH 3 ] (8 [6]b) in 54% overall yield. 30 This method was used to isolate the isomerically pure 5 [10]a in an overall unoptimized yield of 22%, based on the parent anion 2a (Table 1) or ∼9%, based on B 10 H 14 . 32 The regioisomeric iodonium zwitterions also demonstrate significant differences in reactivity toward strong nucleophiles in weakly nucleophilic solvents, which can be used for selective transformations of one isomer into the desired derivative in the presence of another.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations